Violence and social injustice against lesbian, gay and bisexual people - Sloan, Lacey M.; Gustavsson, Nora S. (New York : Harrington Park Press, 1998)
Fonds Suzan Daniel (FSD)ook uitgegeven als Journal of Gay & Lesbian Social Services 08(1998) 3
Engels
Monografie